PENCEGAHAN STROKE DINI MELALUI PEMERIKSAAN TEKANAN DARAH, KADAR GULA DARAH DAN KOLESTEROL PADA PINANDITA DI DESA TARO KECAMATAN TEGALLALANG GIANYAR - Swastini, D.A.; Wiryanthini, I.A.D.; Wijayanthi, N.P.A.D.; Samirana, P.O. (Buletin Udayana Mengabdi, 2018)
Stroke is the third highest cause of death in Indonesia. Hypertension, diabetes mellitus, and hypercholesterolemia is a major risk factor for stroke that can be modified, where the diagnosis can be confirmed by examination of blood pressure, blood sugar levels, and cholesterol levels. The rise of religious activity resulting changes in activity and lifestyle of priest in Taro Village, Sub-districts of Tegallalang, in Gianyar regency that potentially induce stroke. The activities performed by checking blood pressure (BP), fasting blood glucose (FPG) or the 2-h blood glucose (2-h PG) and blood fasting cholesterol level. Examination followed by 46 pries through Taro village, with the distribution of participants aged between 27 to 63 years. Results showed that 84.44% of total participants have TD above normal on the highest range of 151-200mg / hg, 74.33% of total participants have FPG above normal on the highest range of 151-200 mg/dl, 64.22% for 2-h PG on the highest range 201-250 mg/dl, and 87.63% for blood fasting cholesterol level in on the highest range 251-300 mg/dl. Based on these results, its necessary to follow up by counseling lifestyle modification, and reexamination for a further therapy determination.